1985
DOI: 10.3758/bf03200013
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement-induced recovery of a taste-LiCl association following extinction

Abstract: Water-deprived rats were given a single exposure to saccharin and LiCl, either paired or unpaired. Half the subjects then received three saccharin-only exposures (extinction) in the training enclosure, followed by a single LiCl-onlypresentation (unconditioned stimulus reinstatement) 8 days after conditioning. The remaining subjects received six saccharin-only exposures, followed by LiCI reinstatement 13 days after conditioning. In both cases LiCI reinstatement occurred outside the training/test context. Apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 16 publications
4
48
2
Order By: Relevance
“…One previous experiment using taste-aversion conditioning in rats revealed that a combined increase in the number of extinction trials and the length of the retention interval reduced recovery from extinction following US reinstatement (Schachtman, Brown, & Miller, 1985). However, this taste-aversion experiment did not differentiate between the degree of extinction and the retention interval as the critical factor.…”
Section: Discussionmentioning
confidence: 86%
“…One previous experiment using taste-aversion conditioning in rats revealed that a combined increase in the number of extinction trials and the length of the retention interval reduced recovery from extinction following US reinstatement (Schachtman, Brown, & Miller, 1985). However, this taste-aversion experiment did not differentiate between the degree of extinction and the retention interval as the critical factor.…”
Section: Discussionmentioning
confidence: 86%
“…During reacquisition training, savings is apparent because relearning occurs much faster than original learning (Frey and Ross, 1968;Napier et al, 1992). The existence of savings is among the evidence supporting the notion that extinction training leaves behind residual excitatory strength (Reberg, 1972;Schactman et al, 1985;Kehoe, 1988). Here we present evidence for this residual-plasticity hypothesis in eyelid conditioning and characterize basic mechanisms involved in the savings observed with this form of motor learning.…”
mentioning
confidence: 77%
“…There are abundant examples using a variety of treatments that support such a conclusion. For example: (I) Reminder treatments have proven successful in revealing latent associations in several paradigms, including reinstatement of conditioned taste aversions following extinction (Schachtman, Brown, & Miller, 1985); reinstatement of audiovisual CSs following extinction (Bouton, 1990;Bouton & Bolles, 1979;Rescorla & Heth, 1975); the CS preexposure effect (Kasprow et aI., 1984); performance failures caused by electroconvulsive shock (Miller et aI., 1974); infantile amnesia (Campbell & Jaynes, 1966); and spontaneous forgetting (Deweer et aI., 1980). (2) Long retention intervals between training and testing have produced attenuation ofextinction (Pavlov, 1927) and the CS preexposure effect (Kraemer, Randall, & Carbary, 1991).…”
Section: Resultsmentioning
confidence: 99%